2014
DOI: 10.1353/hpu.2014.0041
|View full text |Cite
|
Sign up to set email alerts
|

The Health and Health Behaviors of a Sample of African American Pastors

Abstract: There is growing concern for the health status of clergy in light of recent studies showing high rates of chronic health conditions and obesity. This manuscript examined the health and health behaviors of South Carolinian African Methodist Episcopal (AME) pastors (n=40). A majority of pastors were overweight or obese (93%) with hypertension (68%); half had two or more chronic health conditions, 35% had high cholesterol, 30% arthritis, and 20% diabetes. On average, pastors had a waist circumference that put the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 42 publications
(59 reference statements)
0
26
0
Order By: Relevance
“…It was expected that individuals electing to attend a health-focused conference and those involved in health promotion activities within their respective congregations would demonstrate a greater degree of optimal health behaviors than the larger communities that they serve. Similarly, Baruth and colleagues demonstrated suboptimal physical activity and fruit and vegetable consumption among African-American pastors (Lumpkins et al 2013;Baruth et al 2014). Poor health outcomes in 2 geographically separate African-American congregations correlated directly with their health attitudes and beliefs reaffirming the need for health education and promotion in the African-American church (Lewis and Green 2000).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It was expected that individuals electing to attend a health-focused conference and those involved in health promotion activities within their respective congregations would demonstrate a greater degree of optimal health behaviors than the larger communities that they serve. Similarly, Baruth and colleagues demonstrated suboptimal physical activity and fruit and vegetable consumption among African-American pastors (Lumpkins et al 2013;Baruth et al 2014). Poor health outcomes in 2 geographically separate African-American congregations correlated directly with their health attitudes and beliefs reaffirming the need for health education and promotion in the African-American church (Lewis and Green 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible that our findings are consistent with the fact that pastors and health ministry leaders face challenges engaging in healthy lifestyle practices such as following a healthy diet and maintaining a regular physical activity regime. Prior studies show that the health behaviors of clergy are poor due to the high physical and emotional demands of their profession (Webb et al 2013;Baruth et al 2014Baruth et al , 2015Lindholm et al 2016). One study indicated clergy had high self-reported good health despite actually having a high prevalence of chronic health conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations